Impact of Climate Change on the Winter Wheat Productivity Under Varying Climate Scenarios in the Loess Plateau: An APSIM Analysis (1961–2100) - Donglin Wang; Mengjing Guo; Jipo Li; Siyu Wu; Yuhan Cheng; Longfei Shi; Shaobo Liu; Jiankun Ge; Qinge Dong; Yi Li; Feng Wu; Tengcong Jiang (Agronomy)
Consideration of crop yield variability caused by long-term climate change offers a way to quantify the interplay between climate change, crop growth, and yield. This study employed the APSIM model to simulate the potential winter wheat yield under varying climate scenarios in 1961–2100 in the Loess Plateau. It also evaluated the long-term response and adaptation differences of winter wheat yield to climate change. The results show that there is a slight downward trend in inter-annual precipitation during the winter wheat growth period, with a reduction of −2.38 mm·decade−1 under the S245 scenario (abbreviated SSP2-4.5) and −2.74 mm·decade−1 under the S585 scenario (abbreviated SSP5-8.5). Interestingly, the actual yield of winter wheat was positively correlated with precipitation during the growth period but not with temperature. By contrast, climatic yield exhibits a significant correlation with both factors, suggesting that future crop yield will largely depend on its sensitivity to climate change. In addition, climate change may marginally improve yield stability, although regional variations are evident. Notably, potential yields in water-restricted areas, such as Qinghai and Gansu, are significantly influenced by precipitation. This study provides an important reference for formulating long-term adaptation strategies to enhance the resilience of agricultural production against climate change.